MAKNA SYURA’ DALAM AL-QUR’AN DAN RELEVANSINYA TERHADAP PRINSIP–PRINSIP DEMOKRASI - Sumini, Adyatama Fajar (Jurnal Al I'jaz, 2023)
Syura as part of the face of Islamic democracy. Its position as a representation of the Eastern civilization system has clashed with the dynamics of the times. Democracy is a dynamic system while Syura is still struggling with its classic face. The fact is that syura is considered a product of the past and cannot accept the developments of the times, especially when compared to democracy today. Often the meaning of syura is taken from classical interpretations that are considered irrelevant to the principles of democracy today. So what is the true interpretation of syura? Can the syura interpretations in the Qur'an give birth to a representative concept? And what is the relevance of the syura interpretations to the principles of democracy? Comparatively, the need for an in-depth process to find answers to this problem. This study shows that syura is the activity of exchanging ideas and asking for good opinions from fellow stakeholders or with more trustworthy parties. Syura emphasizes the existence of maslahah and the obligation to carry out the duties of each individual. When compared to syura in classical and contemporary interpretation, the classical interpretation includes a broader understanding because it is strengthened by other supporting evidence. It is necessary to trace classical to contemporary interpretations in order to give birth to a complete concept.